The mechanism of the social state and the place of the pension system in it: theoretical and legal aspects - S. S. Polesov (Law and Safety)
The article is devoted to the theoretical and legal study of the role and place of the pension system in the mechanism of the social state on the example of the modern Ukrainian legal experience. Based on the analysis of legislation, doctrinal positions and practice of the Constitutional Court of Ukraine, the author has formulated the own vision of the substantive and ontological core of pension provision. It is demonstrated that pension provision as a set of legal relations and a real legal phenomenon in the substantive and ontological dimension cannot be identified either with the process of providing an individual with a set of certain social and material services (procedural approach), or with a set of measures taken by the State to meet the needs of an individual for adequate material security upon reaching retirement age or due to adverse social circumstances which exclude their opportunities for active participation in economic and social life. According to the human-centred paradigm, the substantive and ontological essence of pension provision is not only the right (legal possibility) to demand from the state a certain level of pension payments in accordance with certain objective criteria, but also the real possibility to receive such payments in the amount that allows a person to maintain a decent existence, to ensure their key needs in life and social environment, avoiding poverty and social isolation.